Rubber agroforestry system in Indonesia: Past, present, and future practices - Agustina D.S.; Oktavia Fetrina (E3S Web of Conferences, 2021)
Indonesia is the second largest rubber producing country after Thailand. The area of rubber in 2018 was about 3.7 million hectares with the total production of 3.6 million tons. Among those areas, 88.13% were owned by smallholders, and the rest belongs to private estate (5.16%) and government estate (6.7%). Productivity is still become the problem at smallholders’ level. Some efforts have been conducted in order to improve the productivity of smallholders. The concept of agroforestry has become increasingly relevant in recent days as they introduced new commercial opportunities to smallholders. Agroforestry, with its multiple environmental and economic benefits, can help the agriculture and forestry sectors find innovative solutions to present-day problems: including low profitability, environmental impacts, and negative public perception This paper presents the implementation of rubber agroforestry system at the smallholders’ level since the past, current situation and future scenario for agroforestry in order to support the sustainability of rubber smallholders.